HUBUNGAN ANTARA SAFETY CLIMATE DAN PERCEIVED BARRIER DENGAN UNSAFE BEHAVIOR PADA KARYAWAN BAGIAN PRODUKSI PT X PASURUAN, INDONESIA - Saraswati, Fadilla Ully (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
A growing industry canât be separated from the role of Health and Safety. In Fact, they are found unsafe behavior in a company engaged in the production of food, such efforts neglect of work instruction, reluctance to use PPE (Personal Protective Equipment) in accordance with procedures, and do not obey the rules that have been listed in the company. Based on the above results, there is a presumption that there is a relationship between the initial climate and perceived safety barrier with unsafe behavior on the production employees of PT X Pasuruan, Indonesia. The purpose of this study was to examine the relationship between climate and perceived safety barrier with unsafe behavior. The subject of research is the production employees of PT X Pasuruan, Indonesia (N = 41). This study uses incidental sampling technique. Data analysis technique using Spearman correlation test. The test results showed that the relationship is a significant negative correlation between safety climate and unsafe behavior (r = -.680 and p (0.000) <0.05), and there is a significant positive relationship between perceived barriers and unsafe behavior (r = .704 and p ( 0.000) <0.05). Based on this research, the company needs to open up insights on employees by emphasizing safety as the highest basis for creating a safe and comfortable working environment